Sexual orientation and psychotic-like experiences among Chinese college students: the role of gender - Lu, Dali; Qing, Zaihua; Tu, Ying; Liu, Xiaoqun (Frontiers in Psychiatry, 2023)
Objective The mental health of sexual minorities has received increasing attention, but there are few studies on the risk of psychotic-like experiences (PLEs) among sexual minorities. The purpose of this study is to explore the relationship between different sexual orientations and PLEs among college students and the moderating effect of gender. Methods A total of 4,460 college students from seven provinces participated in this cross-sectional survey. The χ2 test and logistic regression were used to investigate the relationship between sexual orientation and PLEs. Results Of the participants, 4.9% identified as bisexual, 1.1% as lesbian/gay, and 5.6% were questioning/unsure; 60.1% of the sample experienced at least one PLE item, 59.2% reported delusional experiences (DEs), and 20.6% had hallucinatory experiences (HEs). Compared with heterosexual college students, bisexual and questioning students showed a higher risk of PLEs, DEs, and HEs, and lesbian/gay students showed a higher risk of HEs. Stratified analysis indicated that sexual orientation was significantly associated with PLEs only for female college students. Conclusion Sexual orientation is a predictive factor of PLEs. In particular, different sexual minority subgroups show the different effects on PLEs between male and female college students. Mental health interventions for PLEs could employ distinct strategies based on different sexual orientations and gender disparity.